Blast Response of Segmented Bored Tunnel using Coupled SPH–FE Method. (June 2015) - Koneshwaran, Sivalingam; Thambiratnam, David P.; Gallage, Chaminda
Abstract: Underground transport tunnels are vulnerable to blast events. This paper develops and applies a fully coupled technique involving the Smooth Particle Hydrodynamics and Finite Element techniques to investigate the blast response of segmented bored tunnels. Findings indicate that several bolts failed in the longitudinal direction due to redistribution of blast loading to adjacent tunnel rings. The tunnel segments respond as arch mechanisms in the transverse direction and suffered damage mainly due to high bending stresses. The novel information from the present study will enable safer designs of buried tunnels and provide a benchmark reference for future developments in this area. Highlights: Coupled SPH/FEM was used to treat blast response of segmented bored tunnel. Present results compared well with those from above and below ground experiments. Segments in the tunnel rings respond as arch mechanism in transverse direction. Circumferential joints are more likely to fail than radial joints under the blast. Segments were damaged mainly due to the high bending stress caused by blast load.